Pediatric Obstructive Sleep Apnea: Knowledge and Attitudes of Medical and Dental Students and Fresh Graduates from Saudi Arabia - Lamyaa N. Alharbi; Mashail A. Alsaikhan; Sanaa N. Al-Haj Ali; Ra'fat I. Farah (MDPI AG, 2021)
This study aimed to assess the knowledge level and attitudes of graduating Saudi medical and dental students and fresh graduates from those faculties about pediatric obstructive sleep apnea (OSA), and the relation of their knowledge level to sociodemographic variables. In this cross-sectional study, 722 graduating students and fresh graduates were requested to answer a questionnaire pretested for validity and reliability. The data were analyzed statistically. Results revealed that medical participants scored 15.45 (out of 22), with 38% of them showing good knowledge about pediatric OSA, while dental participants scored 14.59, with 25.2% of them showing good knowledge. By regression analysis, medical participants (odds ratio (OR): 1.529) were more likely to have good knowledge than dental participants, while participants who belonged to institutions located in the central region (OR: 0.546) were less likely to have good knowledge than those from southern region institutions. In addition, participants from public institutions (OR: 0.290) were less likely to have good knowledge than those from private institutions. Regarding attitudes, medical participants scored 14.13 (out of 20), and dental participants scored 14.64. We detected a significant positive correlation between knowledge and attitude scores of dental participants. Given these findings, the knowledge level of graduating Saudi medical and dental students and fresh graduates about pediatric OSA was not optimal. The college type, institution sector, and location in the kingdom were factors associated with good knowledge. There is a need for further education and training about pediatric OSA in the undergraduate Saudi medical and dental curricula and continuing professional development programs about the topic after graduation.